Elevated serum sodium in recipients of liver transplantation has a substantial impact on outcomes. (14th September 2021) - McDonald, Malcolm F.; Barrett, Spencer C.; Malik, Tahir H.; Anand, Adrish; Keeling, Stephanie S.; Christmann, Caroline R.; Goff, Cameron R.; Galvan, Thao; Kanwal, Fasiha; Cholankeril, George; Goss, John; Rana, Abbas
Summary: Dysnatremias are a rare but significant event in liver transplantation. While recipient pre‐transplant hypernatremia has been demonstrated to increase post‐transplant mortality, the degree of hypernatremia and the impact of its resolution have been less well characterized. Here, we used multivariate Cox regression with a comprehensive list of donor and recipient factors in order to conduct a robust multivariate retrospective database study of 54, 311 United Network for Organ Sharing (UNOS) liver transplant patients to analyze the effect of pre‐transplant serum sodium on post‐transplant mortality, post‐transplant length of hospitalization, and post‐transplant graft survival. Mortality and graft failure increased in a stepwise fashion with increasing pre‐transplant hypernatremia: 145 −150 mEq/L (HR = 1.118 and HR = 1.113), 150–155 mEq/L (HR = 1.324 and HR = 1.306), and > 155 mEq/L (HR = 1.623 and HR = 1.661). Pre‐transplant hypo‐ and hypernatremia also increased length of post‐transplant hospitalization: < 125 mEq/L (HR = 1.098), 125–130 mEq/L (HR = 1.060), 145 −150 mEq/L (HR = 1.140), and 150–155 mEq/L (HR = 1.358). Resolution of hypernatremia showed no significant difference in mortality compared with normonatremia, while unresolved hypernatremia significantly increased mortality (HR = 1.254), including a durable long‐term increased mortality risk for patients with creatinine < 2 mg/dL and MELD < 25. Pre‐transplant hypernatremia serves as a morbid prognostic indicator for post‐transplant morbidity and mortality. Abstract : Pre‐transplant elevated serum sodium in liver transplant recipients led to increased mortality, decreased graft survival, and prolonged hospital stay. Resolution of hypernatremia provides durable mortality benefit even for preserved renal function and low MELD.